Edukasi Cegah Anemia dengan Konsumsi Zat Besi dan Gaya Hidup Sehat pada Remaja Putri di SMP Swasta Imelda - Maidina Putri; Khairani Khairani (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Adolescent girls are a group vulnerable to anemia. To address the problem of anemia in adolescents, the government is implementing a program to provide iron supplement tablets (TTD) to every teenager in all schools in Indonesia. The purpose of this Community Service program is to provide education on preventing anemia by consuming iron and living a healthy lifestyle to adolescent girls at Imelda Private Middle School in Medan in 2026. The implementation method for this Community Service program is in the form of education, counseling on preventing anemia by consuming iron and living a healthy lifestyle. The implementation of this Community Service program is divided into 3 parts, namely, activity preparation, activity implementation and evaluation. The results of this Community Service program on the level of knowledge of the participants are seen from the results after being given knowledge about anemia and healthy lifestyle patterns, namely in the less category for 17 respondents (63%), after being given socialization and re-measured, the post-test results obtained were that most understood knowledge about anemia and lifestyle patterns, namely in the good category for 25 respondents (93%).